UPAYA MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN DENGAN MENGGUNAKAN MODEL DRILL PADA MATA PELAJARAN AL-QUR’AN HADITS DI KELAS VII MTs PONPES TAJUSSALAM - Nurjannah Khairani; Muamar Al Qadri; Ahmad Fuadi (STAI Jama'iyah Mahmudiyah Tanjung Pura, 2023)
This is due to the use of methods in conveying subject matter used by teachers who still tend to use conventional methods (lectures and question and answer) and students are still seen as passive student objects because learning activities are still teacher centered (teacher center). The conclusions from the implementation of this research are: The reading achievement of class VII students of MTs Ponpes Tajussalam for the 2022/2023 Academic Year has increased by using the Model Drill strategy in the Al-Qur'an Hadith subject, specifications for understanding Al-Qur'an reading material from the data conclusions obtained ie In the first cycle completeness reached 56.55% of students. In cycle II, the percentage of completeness was achieved by 63.64%, an increase of 7.8% from the pre-cycle. In cycle III, the percentage of learning completeness was achieved by 78.8%, there was another increase of 15% from cycle I. In Cycle III, the learning completeness was 90, 3% increased from cycle II. So from pre cycle to cycle III there is an increase in level of 33.7%